(untitled) (Bangladesh Journal of Otorhinolaryngology, 2021)
Objectives: To see the hearing outcomes following Type III tympanoplasty with stapes columella grafting after canal wall down mastoidectomy and find out the recurrence rates in patients undergoing this procedure. Methods: This prospective observational study includes 120 cases undergoing Type III tympanoplasty with stapes columella grafting following canal wall down mastoidectomy for cholesteatoma at a tertiary care center from 2018 to 2020. Patient charts were reviewed for demographic data, diagnosis, and operative details. Patients were included in statistical analysis if they were found to have undergone the aforementioned procedure. Evaluation of hearing improvement was made by comparing preoperative air-bone gap (ABG) and ABG at follow-up at 6 months and 1 year postoperatively. Results: One hundred and twenty patients were included for this study. Erosion of the otic capsule, posterior fossa plate, or tegmen was noted in 20% of cases, highlighting disease severity. One hundred and two (85%) had undergone prior otologic surgery. Mean time to short-term follow-up was 6 ± 3 months. The average short-term ABG was 25 ± 12 dB HL; 36% achieved an ABG <20 dB and thirteen had follow-up at least 1 year postoperatively (mean = 33 ± 16 months). At longer-term follow-up, mean ABG was 24 ± 11 dB HL. Hearing remained stable over time (P = .26). Conclusion: In some patients undergoing canal wall down mastoidectomy for advanced or recurrent cholesteatoma, Type III tympanoplasty with stapes columella grafting yields marginal hearing benefit. Bangladesh J Otorhinolaryngol 2021; 27(2): 145-151